Dragon rider - Funke, Cornelia Caroline (New York : Scholastic, 2004)
After learning that humans are headed toward his hidden home, Firedrake, a silver dragon, is joined by a brownie and an orphan boy in a quest to find the legendary valley known as the Rim of Heaven, encountering friendly and unfriendly creatures along the way, and struggling to evade the relentless pursuit of an old enemy.
Originally published in German under the title Drachenreiter, by Cecilie Dressler Verlag, Hamburg, Germany in 1997.
Keywords: Fantasy; Dragons -- Fiction; Animals, Mythical -- Fiction